2013
DOI: 10.1111/apt.12377
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: vitamin D and non-alcoholic fatty liver disease

Abstract: NAFLD patients have decreased serum 25(OH)D concentrations, suggesting that vitamin D may play a role in the development of NAFLD. The directionality of this association cannot be determined from cross-sectional studies. Demonstration of a causal role of hypovitaminosis D in NAFLD development in future studies could have important therapeutic implications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
176
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 236 publications
(197 citation statements)
references
References 56 publications
8
176
1
2
Order By: Relevance
“…Nevertheless, additional analysis performed in our study showed lower concentration level of the fibroblast growth factor 19 (FGF19) in patients with hypovitaminosis D. Fibroblast growth factor 19 (FGF19) is a hormone released from the small intestine; recently, it has emerged as an endocrine regulator of glucose and lipid metabolism. The results of the presented study, although not statistically significant, need particular attention, since a decrease in fasting FGF19 is an independent risk factor for the development of NAFLD in obese adolescents [23,24,25]. Its relationship to vitamin D deficiency needs further investigation.…”
Section: Meanmentioning
confidence: 64%
“…Nevertheless, additional analysis performed in our study showed lower concentration level of the fibroblast growth factor 19 (FGF19) in patients with hypovitaminosis D. Fibroblast growth factor 19 (FGF19) is a hormone released from the small intestine; recently, it has emerged as an endocrine regulator of glucose and lipid metabolism. The results of the presented study, although not statistically significant, need particular attention, since a decrease in fasting FGF19 is an independent risk factor for the development of NAFLD in obese adolescents [23,24,25]. Its relationship to vitamin D deficiency needs further investigation.…”
Section: Meanmentioning
confidence: 64%
“…25 No 2: 175-181 peroxisome proliferator-activated receptor gamma (PPAR-γ) [12,13]. Although not all [14,15], many observational studies report associations between vitamin D deficiency and hepatic steatosis [12,16], the aggregate effect of which has been illustrated in a meta-analysis [17] confirming the presence of decreased serum 25-hydroxyvitamin D concentrations in such patients. Specifically, they were 26% more likely than healthy controls to be vitamin D deficient.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of NAFLD in obese children is estimated to be between 36 and 44%, regardless of the method used to diagnose the disease (4,5). It is worth noting that VD deficiency is more common in obese subjects than in normal-weight subjects (6). Furthermore, a recent meta-analysis has shown that NAFLD patients have decreased serum VD levels (7).…”
Section: Introductionmentioning
confidence: 99%